University Values-Based Quality Assurance System; Model Quality Control and Quality Development in Universitas Islam Bandung (Unisba) - Yanti Nurdiyanti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The purpose of this study is to explore; 1) University Values-Based Quality Assurance System (integration of Islamic values ​​in the internal quality assurance system), 2) Quality Control and Quality Development Model in the value-based quality assurance system, 3) Implications of implementing a value-based quality assurance system to strengthen the quality of Islamic Higher Education at the Islamic University of Bandung (UNISBA). The research approach used in this study is qualitative with a case study type. Data collection techniques were carried out through semi-structured interviews and documentation. Data analysis techniques used the Miles and Huberman analysis technique, while the validity of the data was guaranteed through credibility testing with source and method triangulation techniques. The results of the study found that; 1) The integration of Islamic values ​​(spirit of Islam) in SPMI at UNISBA is institutionalized systemically through the establishment of 47 quality standards and the implementation of the PPEPP cycle, so that the values ​​of amanah, ihsan, and itqan function as an ethical and operational framework in internal quality assurance. 2) The value-based quality assurance model is implemented through the integration of Quality Control (standard control, internal quality audits, and performance monitoring) and Quality Development (OBE-based learning innovation, research strengthening, HR development, and internationalization) which complement each other and are oriented towards continuous quality improvement. 3) The implications of implementing a value-based quality assurance system are seen in strengthening governance and quality culture, improving academic and non-academic quality, and increasing institutional competitiveness as demonstrated by the achievement of superior accreditation, quality certification, and international accreditation progress.